Mouse strains to study cold-inducible beige progenitors and beige adipocyte formation and function - Daniel C. Berry (Nature Portfolio, 2016)
Beige adipocytes are formed in response to cold and thought to contribute to organismal energy homeostasis. Here, the authors study a range of conditional and inducible RFP-expressing Cre mouse strains and find that SMA-based lines are the most useful for mapping beige adipocyte progenitor cells.